2020
DOI: 10.1038/s41598-020-58306-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum gamma-glutamyltransferase activity and Parkinson’s disease risk in men and women

Abstract: We evaluated serum gamma-glutamyltransferase (GGt) and the risk of parkinson's disease (pD). Using data from the National Health Insurance Service (NHIS) database, we constructed a cohort consisting of individuals aged above 40 years who underwent a health check-up in 2009. After excluding individuals with heavy alcohol consumption, hepatobiliary and pancreatic disorders, and a previous history of PD, each quartile group of baseline serum GGT levels was monitored for the development of PD for 7 years. Adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Our study found an association between higher GGT and higher risk of cognitive impairment in the female population, which is consistent with previous studies in the male population (Kunutsor and Laukkanen, 2016 ). A study of GGT and Parkinson's disease is also consistent with our finding, that GGT may contribute to neurodegenerative disease in the female population (Yoo et al, 2020 ). However, contrary to our findings, a genetic study found no clear link between GGT and cognitive function (Kunutsor et al, 2018 ), possibly because that study did not include a subgroup analysis based on sex, which is essential because of the finding from previous study that estrogen may affect GGT activity in the body (Zarida et al, 1994 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found an association between higher GGT and higher risk of cognitive impairment in the female population, which is consistent with previous studies in the male population (Kunutsor and Laukkanen, 2016 ). A study of GGT and Parkinson's disease is also consistent with our finding, that GGT may contribute to neurodegenerative disease in the female population (Yoo et al, 2020 ). However, contrary to our findings, a genetic study found no clear link between GGT and cognitive function (Kunutsor et al, 2018 ), possibly because that study did not include a subgroup analysis based on sex, which is essential because of the finding from previous study that estrogen may affect GGT activity in the body (Zarida et al, 1994 ).…”
Section: Discussionsupporting
confidence: 92%
“…We also asked them about their menstrual history to see if they had gone through menopause and their age at menopause. According to self-reported information, alcohol consumption was classified as heavy drinker (alcohol consumption ≥30 g/day), mild-moderate drinker (alcohol consumption <30 g/day) or abstainer (alcohol consumption = 0 g/day) (Yoo et al, 2020 ), and smoking status was classified as non-smoker or having quit more than 1 year ago or current smoker or having quit <1 year ago. BMI was defined based on the measured height and weight and calculated as weight (kg)/height (m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Last but not least in importance, GGT levels seem to affect the risk of stroke. The positive relationship between GGT concentrations and stroke were presented in a few independent studies [ 47 , 104 ]. Furthermore, a meta-analysis including 5707 stroke cases among 926,497 participants in 10 prospective studies stated that GGT level is an independent stroke risk factor [ 47 ].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…GGT is a key player in glutathione metabolism, which is an essential cellular antioxidant [ 38 ]. GGT is a commonly used diagnostic test to assess liver function [ 104 ]. Yet, its role may be underestimated in pathologies of other systems, including diabetes and neurodegenerative diseases [ 39 ].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…This study included six cohort studies (6,7,9,(15)(16)(17), four cross-sectional studies (18)(19)(20)(21), and one case-control study (22). The locations of the included studies (N=11) were as follows: three studies, South Korea (6,7,15); two studies, the United States of America (19,20); one study, Israel (18); one study, South Africa (22); one study, China (16); one study, Canada (17); one study, Italy (21); and one study, Finland (9) (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%